Pencegahan perkawinan sebagai upaya perlindungan hukum terhadap anak - Najiya, Usluki (Maliki Interdisciplinary Journal, 2024)
Marriage prevention is a step in preventing marriage from occurring. In Islamic Civil Law in Indonesia, marriage prevention is regulated in Law No. 1 of 1974 Article 13 which states, "Marriage can be prevented if there is a party who does not meet the requirements for marriage." The inability to meet these requirements refers to two aspects, namely administrative requirements and substantive requirements. Administrative requirements relate to matters related to marriage administration, such as the procedures mentioned earlier. While substantive requirements relate to fundamental matters, the existence of cases that prohibit marriage.